Peran Edukasi Finansial dalam Membentuk Kesadaran Investasi Generasi Z - Putri Dini Agustin; Dhea Dinanty; M. Sawal Pitriyadi; Zulkarnain Abdurrahman; Tuti Anggraini (BADAN PENERBIT STIEPARI PRESS, 2025)
Financial education activities for Generation Z are crucial for fostering investment awareness from an early age. This article discusses the implementation of the Generation Z Financial Education outreach program: